DETERMINAN TAX MORALE PADA ORANG PRIBADI NON KARYAWAN: STUDI EMPIRIS PADA MITRA GO-JEK INDONESIA - Lestari Kurniawati; Sifit Dwi Nurcahyo (Direktorat Jenderal Pajak, 2022)
The contribution of income tax for individuals other than those who work as employees (PPh 25/29 OP) is only about 1% in the last seven years. It requires tax awareness and voluntary tax compliance of individuals doing independent work. This study aims to examine eight independent variables that influence tax morale as an important determinant of voluntary tax compliance. This study used the mix method by testing empirical data questionnaires on respondents of Go-Jek Indonesia partners.. The selection of this group is relevant because they have a greater chance of doing tax evasion. The results of this study indicate that the factor that most influences the tax morale of Go-Jek Indonesia's partners is the reference group. Perceptions of the level of government corruption, the efficiency of government spending, and personal interests also have a significant effect on tax morale. Meanwhile, perceptions of fairness, tax rate levels, financial difficulties, and the possibility of being examined and subject to punishment do not have a significant effect on the tax morale of Go-Jek Indonesia's partners. This can be a reference for collecting tax revenues through a more persuasive approach.